The Role of IoT and Smart Technologies in Enhancing Employee Well-being and Productivity - Radha, P; Bhanumathi, P; Priya, A; Rajnarayanan, B (Apex Journal of Business and Management, 2025)
This research explores how IoT and smart technologies contribute to enhancing employee well-being and productivity by utilizing real-time monitoring systems, predictive analytics, and automated workplace solutions. It focuses on optimizing work environments, improving energy efficiency, and fostering a more employee-centric approach in smart cities in India. The study employs both descriptive and exploratory research designs, incorporating insights from experts, HR analysts, and regular employees in service organizations. Key independent and dependent variables were identified, and multiple regression analysis was conducted using SPSS software to analyze the impact of IoT-driven solutions on employee well-being and productivity. The findings highlight a positive correlation between IoT-enabled workplace innovations and improved employee engagement, well-being, and efficiency. The integration of HR analytics with IoT applications facilitates better resource management, real-time monitoring, and personalized work environments, leading to enhanced productivity. The study presents a strategic framework for HR professionals to integrate IoT and smart technologies into employee well-being and productivity initiatives. It emphasizes the importance of collaboration, data-driven decision-making, and the development of robust privacy and security policies to ensure ethical and effective implementation.